The Effect of Advertising on social media on Fashion Product Purchase Decision - Adri Nur Alamsyah; Egi Lank Masken; Andre Prasetyo (International Journal of Research and Applied Technology (INJURATECH), 2023)
Technology makes the fashion industry grow very rapidly and nowadays fashion has become a lifestyle for people to show social status. The many local and international brands that exist, trigger the desire to use fashion products. As if you don't want to be left behind with existing trends. In this modern era, social media is very helpful in everyday life, especially for producers and consumers. Social media has become a gathering place for various communities. In this modern era, product purchase decisions are strongly influenced by social media such as Facebook, Twitter, YouTube, Pinterest, WhatsApp, Instagram and TikTok. This study aims to determine the effect of advertising on social media on purchasing decisions for fashion products. This research uses a combination of quantitative and qualitative methods. Children's questionnaires were distributed to 100 people. Questionnaires will be distributed to students as case studies. The results showed that advertising in social media had an effect on purchasing decisions for fashion products. Humans are greatly facilitated by the existence of technology. Various media with different and complete features are very helpful for those of us who want to promote a business. The development of the fashion industry is very fast, supported by the development of existing technology, social media has evolved into an efficient and practical platform in marketing. This study concludes that advertising on social media is very influential, especially in the form of visuals in the form of promos and other information about the products being sold. This research is expected to help get more potential consumers by utilizing social media.